DESIGN AND IMPLEMENTATION OF AN EDUCATIONAL QUIZ TO PROMOTE RELIGIOUS MODERATION AMONG PRIMARY SCHOOL STUDENTS - Ridwan, Muhammad; Lasimin; Ropiudin; Syska, Kavadya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study explores the design and implementation of an educational quiz aimed at promoting religious moderation among primary school students. The quiz, consisting of 50 multiple-choice questions across five thematic areas—tolerance and respect for differences, peaceful coexistence, anti-violence, love for the nation and diversity, and friendship and togetherness—was implemented with students in grades 3 to 6 at MI Ma’arif NU 1 Kracak, Cilacap. The study employed a quasi-experimental design with pre- and post-test assessments to evaluate changes in students' knowledge, attitudes, and behaviors. Classroom observations and student reflections were also used to gain deeper insights into the impact of the quiz. The results indicate a significant increase in students’ knowledge of religious moderation after participating in the quiz, as well as positive changes in attitudes and behaviors related to tolerance, empathy, and respect for diversity. The interactive features of the quiz, including immediate feedback and friendly competition, were found to enhance student engagement and motivation. Teachers reported that the quiz encouraged open discussions about sensitive topics, such as interfaith relations and cultural diversity, fostering a more inclusive classroom environment. The findings suggest that game-based learning, particularly through interactive quizzes, can be a powerful tool for instilling values of tolerance and social harmony in primary education. This study highlights the potential of integrating quiz-based interventions into school curricula to promote religious moderation and prepare students for life in multicultural societies. Future research is recommended to explore the long-term impact of such interventions and examine their scalability across different educational contexts.